The Teaching of Pope Francis About Synodality in the Context of Contemporary Theological and Ecumenical Reflection - Bujak, Janusz (Collectanea Theologica, 2021)
The article deals with the ecclesiology of the local Church and synodality. Both topics have been present in Catholic theology since the time of the Second Vatican Council, which laid the foundation for the ecclesiology of the local/particular Church, collegiality of bishops and synodality. This ecclesiology was developed both theoretically and practically in the post-conciliar period, but there are some theologians who believe that during the pontificate of John Paul II there was a return to the universalist ecclesiology, as evidenced by the documents published by the Roman Curia, especially Communionis notio. Pope’s Francis teaching on synodality and strengthening the Church at local and regional levels addresses the demands of those theologians who believe that Chapter III of the Lumen Gentium Constitution has not yet been properly implemented. The Pope emphasizes, that synodality is a constitutive dimension of the Church and therefore what the Lord is asking of us is already in some sense fully present in the word “synod” itself.